Moller's essentials of pediatric cardiology - Johnson, Walter H., Jr.; Hebson, Camden L. (Hoboken, NJ : Wiley-Blackwell, 2023)
"Caring for children with heart disease is extremely complex, requiring a different and often tailor-made approach compared with adults with similar cardiac problems. From history-taking, physical examination, ECG, and chest X-ray -- the basics that enable clinicians to uncover possible problems and eliminate areas of false concern -- this essential guide goes on to examine the range of more complex topics in the diagnosis and treatment/management of childhood cardiovascular disease"--
Tools to diagnose cardiac conditions in children -- Environmental and genetic conditions associated with heart disease in children -- Classification and physiology of congenital heart disease in children -- Anomalies with a left-to-right shunt in children -- Conditions obstructing blood flow in children -- Congenital heart disease with a right-to-left shunt in children -- Unusual forms of congenital heart disease in children -- Unique cardiac conditions in newborn infants -- The cardiac conditions acquired during childhood -- Abnormalities of heart rate and conduction in children -- Congestive heart failure in infants and children -- A healthy lifestyle and preventing heart disease in children
Preceded by: Pediatric cardiology / Walter H. Johnson Jr., James H. Moller. Third edition. 2014
Keywords: Pediatric cardiology; Heart -- Diseases; Heart Diseases; Child; Electronic books; Handbook; Handbooks and manuals